Reciprocal regulation between m6 A modifications and non-coding RNAs: emerging roles in cancer therapeutic resistance - Dan Fan; Yan Shang; Yating Cong; Yanlin Jiao; Na Li; Hailong Zhao (Discover Oncology)
Abstract In recent years, the interplay between N6-methyladenosine (m6A) modifications and non-coding RNAs (ncRNAs) has emerged as a pivotal research area, owing to their crucial involvement in the pathophysiological mechanisms underlying various diseases. A significant hurdle in cancer therapy is therapeutic resistance, which frequently contributes to adverse patient outcomes. Recent investigations have underscored the vital role that interactions between m6A modifications and ncRNAs play in mediating cancer therapeutic resistance via the MAPK, PI3K/Akt/mTOR, Wnt/β-catenin, HIPPO, and NF-κB pathways. This review elucidates how these interactions drive tumor therapeutic resistance by modulating these pathways. By dissecting the regulatory dynamics between m6A and ncRNAs in the context of cancer therapeutic resistance, this review aims to deepen the understanding of m6A-ncRNA interaction in cancer therapeutic resistance and identify potential therapeutic targets to improve cancer treatment efficacy.